Bribery A Social Evil: An Islamic Perspective: رشوت ایک معاشرتی ناسور - Aziz Ullah, Dr. Muhammad; Gul, Dr. Rais; Muhammad, Dr. Badshah (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2021)
It is an inarguable fact that bribery is a social evil and can prove highly fatal to the different institutions of a society. The Holy Quran considers it the major force behind the decline of numerous civilizations and nations of the past. Different nations suffered the wrath and anger of Allah on account of this malignant distemper. The Holy Quran alludes to the fate of these nations and tribes in order to set them example for the followers of prophet Muhammad (SAW) and to warn them about the dire consequences of practicing this evil. As a matter of fact, Muslims should have shunned this notorious practice but contrary to it and as an irony of fate, this menace is flourishing with leaps and bounds under different nomenclatures. The outcome of this can be seen in the worsening economic and religious conditions of the country. From rulers to the subjects, this curse is being carried out in diverse guises and on the pretext of different self-fabricated excuses. This study not only problematizes the issue of bribery in Pakistan but also attempts to highlight it from different angles. The study also suggests certain means of prevention, which if followed both in letter and spirit, will help in the alleviation and containment of the problem.